PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP PENGUASAAN KONSEP DITINJAU DARI KETERAMPILAN BERPIKIR KRITIS PADA MATA KULIAH OPTIK - Hidayat, Samsun; Susilawati, Susilawati; Soeprianto, Harry (Lensa : Jurnal Kependidikan Fisika, 2014)
This study was aimed to analyzethe effect of project based learning model to understanding concepts  and critical thinking skills in optics lecture at undergraduate student of Physics Educational Program of IKIP Mataram in academic year 2013/2014. This study included in quasi experiment with posttest onlycontrol group design. All of 75 populations are included as sample. The datawere analyzed with multivariate analysis (MANOVA).The conclusion can be stated based on analysis result is (1) project based learning model having an effect on understandingconcepts of undergraduate students ((Fcal = 37,88 > Ftable = 3,91), with pvalue<0,05. (2) project based learning model having an effect on critical thinking skill of undergraduate students ((Fcal = 5,47 > Ftable = 3,91), with pvalue<0,05. (3) project based learning model having an effect on both understandingconcepts and critical thinking of undergraduate students ((Fcal = 34,86 > Ftable = 3,91), with pvalue<0,05.